Preferences, Perception, and Pick-Up Order: Unpacking Social Perception and Café Preferences in Urban Padangsidimpuan - Pulungan, Haniful Pasca; Kesuma, Sinar Indra; Lubis, Satia Negara (Universitas Pattimura, 2025)
Amid the rise of café culture in urban Padangsidimpuan, this study examines how socio-economic preferences influence coffee-shop selection, particularly for pick-up orders. A cross-sectional survey involving 312 respondents—selected through stratified random sampling—captured consumer motivations via Likert-scale questionnaires, covering taste satisfaction, ambience, digital convenience, and perceptions of price fairness. Data were analyzed using factor analysis and partial least squares structural equation modelling (PLS-SEM). The results indicate that taste satisfaction (β = 0.33, p < 0.001) and app-based convenience (β = 0.28, p < 0.001) are the strongest predictors of café choice. Ambience contributes indirectly by fostering the intention to share experiences on social media. Segment analysis shows that pick-up customers prioritize convenience nearly twice as much as dine-in patrons, signaling a shift in consumption logic within Indonesia’s secondary cities. These findings extend consumption theory into the realm of secondary urbanization and highlight the role of lifestyle, taste, and digital habitus in shaping emergent consumer publics. This research contributes to the sociology of economic life and offers policy insights for strengthening the local creative economy.